STUDI KASUS MORFOLOGI NANOFIBER POLIVINIL ALKOHOL (PVA) TERHADAP HIDROFOBISITAS PERMUKAAN YANG DINILAI DENGAN PENGUKURAN SUDUT KONTAK - Berly, Yoga Maharesha; Rajagukguk, Tumpal Ojahan; Hendronursito, Yusup (Bhinneka Multidisiplin Journal, 2025)
Nanofiber is a fiber measuring nanometers to micrometers, often used in the medical, energy, filtration, and other fields. The formation of nanofiber with the main ingredient, namely Polyvinyl Alcohol (PVA), this is because of its biodegradable, biocompatible, and chemically stable properties, but has the weakness of being easily degraded when in contact with water. This study examines the effect of electrospinning parameters on the morphology of 10% w/v PVA nanofiber, with parameters namely voltage of 10 and 12 kV, nozzle-collector distance of 10 and 15 cm. Morphological testing was carried out using a Field Emission-Scanning Electron Microscope (FE-SEM) and Contact Angle (CA) test. The test results show that PVA nanofiber has a fiber diameter with a value of NFZ.1; 80 - 406 nm, NFZ.2; 61.7 - 248.9 nm, with a continuous fiber structure and without significant defects, the resulting contact angle value of NFZ.1; 50.05o and NFZ.2; 38.75o, the contact angle value of NFZ.1 is higher than NFZ.2. The nanofiber with the smallest diameter is NFZ.2 and the largest contact angle value is NFZ.1. The results of this research show that the morphology of nanofiber significantly influences the contact angle value.